Palaegeographic evolution of the Kerinthos coastal area (NE Evia island) during the late Holocene - MAROUKIAN, H.; PALYVOS, N.; PAVLOPOULOS, K.; NICOLOPOULOS, E. (Bulletin of the Geological Society of Greece, 2001)
Preliminary results of a detailed study on the palaeogeographic evolution of the Kerinthos coastal archaeological area (N. Evia island) are presented. The coastal setting of Kerinthos has been subjected to important changes during the Late Holocene, under the influence of eustatic sea-level rise, progradation of the Voudhoros river alluvial plain, and tectonic uplift. Subsurface stratigraphie data indicate that Peleki, a naturally sheltered coastal embayment that has been partially infilled by Voudhoros alluvia since at least the Classical period, had been previously a shallow, low-energy brackish water coastal environment - since at least 5000 B.P. Coastal tectonic uplift of the order of 3 m during the last 5 millennia is inferred from 14C dated marsh deposits (0.6 mm/ yr minimum mean uplift rate).